LET’S RAP: IMPROVING STUDENTS’ READING COMPREHENSION - I Made Duta Kharisma; I Gde Putu Agus Pramerta; Anak Agung Putu Arsana (Academic Journal on English Studies (AJOES), 2023)
Reading is faced as a difficult activity to do. The preliminary study presented that the eighth-grade students of SMPN 1 kediri in the academic year 2022/2023 are difficult to identify general information, specific information, textual meaning, and textual reference. Looking at the prior condition, this research aims at knowing the students’ improvement after being treated with read-ask-put (rap) strategy. Therefore, classroom action research was considered to be undergone in two cycles. The instruments were tests and a questionnaire. The data was analyzed by looking at the result of the tests: pre-test and post-tests. The results showed that there occurred improvement from the mean score of the pre-test to the post-tests. It is in line with the result of the questionnaire which showed positive responses. Further rap strategy implementation is needed to be integrated with other language skills.